Foreign Europe as a Significant Other of Russian Identity - O. V. Gaman-Golutvina (Сравнительная политика)
The final issue of Comparative Politics Russia 2023 is predominantly devoted to a discussion of European politics. There is no need to emphasize the relevance of this subject. Historically, Europe has been a significant Other for the intellectual community of Russia, which, following the trends of European culture, oscillated between "Hegelists" and "nihilists," to quote Turgenev's hero.